Impact of household population ageing on carbon emissions: micro-scale evidence from China - Chai, Shijun; Qiao, Hong; Li, Yize (Frontiers in Environmental Science, 2024)
Abstract: Carbon emissions reduction and population ageing are two major challenges faced by human society in the 21st century. Based on data from the China Family Panel Studies (CFPS), we investigated the impact of population ageing on carbon emissions at the household level along with the potential mechanisms of this impact. We found that households with a higher older adult population proportion and age of the household head emitted less, and these results were shown to be very robust and reliable across a series of endogeneity and robustness tests. Furthermore, population ageing contributed to carbon emission reductions for all groups; however, compared with urban households, rural households were more sensitive to population ageing. Mechanism analysis showed that population ageing can reduce household carbon emissions through more frugal life attitudes and lower future income expectations, whereas it increases carbon emissions due to weaker en-vironmental awareness among older adults. However, overall, population ageing has a significant inhibitory effect on household carbon emissions. The findings of this study contribute to our understanding of the mi-cro-scale mechanisms of residents’ carbon emission behaviour and provide new insights for designing targeted policies for carbon reduction from the perspective of population structure.